Two-photon polymerization for 3D biomedical scaffolds: Overview and updates - Jing, Xian; Fu, Hongxun; Yu, Baojun; Sun, Meiyan; Wang, Liye (Frontiers in Bioengineering and Biotechnology, 2022)
The needs for high-resolution, well-defined and complex 3D microstructures in diverse fields call for the rapid development of novel 3D microfabrication techniques. Among those, two-photon polymerization（TPP） attracted extensive attention owing to its unique and useful characteristics. As an approach to implementing additive manufacturing, TPP has truly 3D writing ability to fabricate artificially designed constructs with arbitrary geometry. The spatial resolution of the manufactured structures via TPP can exceed the diffraction limit. The 3D structures fabricated by TPP could properly mimic the microenvironment of natural extracellular matrix, providing powerful tools for the study of cell behavior. TPP can meet the requirements of manufacturing technique for 3D scaffolds (engineering cell culture matrices) used in cytobiology, tissue engineering and regenerative medicine. In this review, we demonstrated the development in 3D microfabrication techniques and we presented an overview of the applications of TPP as an advanced manufacturing technique in complex 3D biomedical scaffolds fabrication. Given this multidisciplinary field, we discussed the perspectives of physics, materials science, chemistry, biomedicine and mechanical engineering. Additionally, we dived into the principles of tow-photon absorption (TPA) and TPP, requirements of 3D biomedical scaffolders, developed-to-date materials and chemical approaches used by TPP and manufacturing strategies based on mechanical engineering. In the end, we draw out the limitations of TPP on 3D manufacturing for now along with some prospects of its future outlook towards the fabrication of 3D biomedical scaffolds.